Bibliometric Analysis of Research Trends in Problem Based Learning (PBL) on Critical Thinking Skills in Science Education for the Period 2015–2025 - Damayanti, Isniwana; Rokhmat, Joni; Muntari, Muntari; Doyan, Aris (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
This study aims to analyze trends in research on the Problem-Based Learning (PBL) model on students' critical thinking skills in science education during the period 2015–2025 through a bibliometric-based systematic review approach. Data were obtained from Google Scholar using the Publish or Perish application and visualized with VOS viewer and analyzed through Dimensions.ai. A total of 1,000 indexed documents were analyzed based on publication year, publication type, target journal, number of citations, and keyword mapping. The results showed that publications related to PBL and critical thinking skills had increased significantly since 2023. Scientific articles dominated the types of publications (80.08%), followed by proceedings and book chapters. Bibliometric visualization showed four main clusters related to the development of learning tools, PBL implementation, learning strategies, and classroom action research. These findings indicate that PBL is increasingly recognized as an effective learning model in developing the critical thinking skills of 21st-century students.